(untitled) (Journal of the College of Education for Women, 2019)
The study examined the assessment of raw water and drinking water projects of Diyala Governorate for the year 2017, amounting to (24) projects, The average per capita supply of potable water (0.396 m3 / day/person), which is less than the global standard for the average per capita of drinking water, and constitute water rumors within the network of water transport in the province (3%), and the water of raw and drinking value within the limits allowed to be used by Iraq and the global indicators of Total acidity, alkaline, acidic function, chlorides, magnesium, Electrical conductivity, total soluble salts, sodium, potassium, sulfates, turbidity other than (raw water). While the index of calcium only a value higher than the limits allowed to be used in Iraq and the world, The percentage of the reduction in the value of indicators for raw water was fluctuated before pumping to citizens for drinking in drinking water projects in the governorate, The highest rate of reduction was recorded for the turbidity index (79.95%), Magnesium (3.7%), acidic function (2.67%), Total precipitation (0.66%), sulfate (0.52%), electrical conductivity (0.41%), Total dissolved salts (0.21%), and there is no reduction (0%) for the indicators (calcium, sodium) together, While the indicators recorded a negative value of reduction (basal-0.77%), chlorides (6.38%), potassium (3.03%), The treatment plant units in these projects do not show the efficiency to remove the pollutants properly.